Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/10790268.2008.11760739
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life in Adults With Spinal Cord Injury

Abstract: Background/Objective: To document the relationship between level of physical activity and quality of life in persons with spinal cord injury. Design: Cross-sectional investigation. Participants/Methods: Men (n ¼ 32) and women (n ¼ 30) with complete and incomplete spinal cord lesions below C6 volunteered to participate in this study. The average length of time since the onset of disability was 9 years (range, 1.5-40 years). Using an interview-formatted survey (Quality of Well-Being Scale), a measure of quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
2
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 15 publications
6
56
2
8
Order By: Relevance
“…4 The PASIPD seems to discriminate between groups of people with different disabilities. The average total PASIPD score (17.8 MET h day À1 ) was comparable to that of other studies that included mostly persons with SCI or elderly with chronic conditions (PASIPD scores varied between 11.0 and 36.3 MET h day À1 ) 4,[11][12][13][14][15][16] (Figure 2). This study used 11 items in contrast to the other studies (12 items).…”
Section: Discussionsupporting
confidence: 81%
“…4 The PASIPD seems to discriminate between groups of people with different disabilities. The average total PASIPD score (17.8 MET h day À1 ) was comparable to that of other studies that included mostly persons with SCI or elderly with chronic conditions (PASIPD scores varied between 11.0 and 36.3 MET h day À1 ) 4,[11][12][13][14][15][16] (Figure 2). This study used 11 items in contrast to the other studies (12 items).…”
Section: Discussionsupporting
confidence: 81%
“…In our study, only the functional outcome was assessed. Physical activity was shown to improve quality of life in human patients with SCI, 60 and this may also be an important factor in the quality of life for dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, helping PSCI maintain high levels of physical fitness and have a healthy and good quality of life is an important research target. Previous studies have demonstrated that PSCI who engage in sports and physical activities show improved physical fitness [1][2][3][4][5] , experience psychological benefits [5][6][7][8] , and have a good health-related QOL (HRQOL) 5,9,10) . It has also been shown that HRQOL improvement associated with physical exercise diminishes once physical exercise is stopped 11) .…”
Section: Introductionmentioning
confidence: 99%